Histological evaluation of placenta in hypertensive pregnancies - Parmar, Kantilal M.; Shah, Gopal V.; Alamchandani, Ravi R. (International Journal of Research in Medical Sciences, 2018)
Background: Maternal and fetal status are reflected in placenta. Toxemia of pregnancy exerts great impact on placenta and thereby fetal and maternal outcomes. Placenta reflects changes of toxemia and these changes are seen morphology as well as histology. Hence study of placenta gives information on the in-utero fetal condition. Methods: A total of 1000 placenta, 500 each from hypertensive and normotensive groups were included in this study conducted in Anatomy Department of SBKS Medical College and Research Centre, Vadodara. Histological evaluation of the samples taken was done under microscope. Results: Microscopic examination of the placenta revealed the presence of calcification, infarction, fibrinoid necrosis, villous hyalinization, syncytial knots and cytotrophoblastic cellular proliferation in both control and hypertension groups. In the present study, calcification was seen in 35.8% in the control group, while the same was seen in 53.8% patients in test group. Fibrinoid necrosis was seen in 48.8% patients in control group as against 69% patients in test group. Villous Hyalinization was seen in 7.40% and 21.4% patients in control and test groups respectively. On the other hand, syncytial knots were seen in 38% and 69% patients in control and test groups respectively. In test group, cytotrophoblastic cellular proliferation was seen in 69% patients while in control group, it was seen in 33.2% patients. Infarction was also seen in test (42.4%) and control (12.6%) groups. Conclusions: Hypertensive disorders of pregnancy have significant effect on the histology of placenta and also influences the fetal outcomes.